Simulation and experiment of rice cleaning in air-separation device based on DEM-CFD coupling method - Ma, Xuedong; Zhao, Lei; Guo, Bingjiang; Dang, He (International Journal of Agricultural and Biological Engineering, 2020)
In order to study the movement characteristics and separation mechanism of rice and its impurities under the action of airflow, and lower the impurity rate in the cleaning operation process, rice and its impurities were modeled based on the “overlapping multi-sphere clump method”, the DEM-CFD coupling method was used to simulate rice cleaning process under different airflow velocity and airflow inclined angle, and combined with aerodynamics, the motion state and separation behavior of rice and its impurities in the flow field. The results showed that under horizontal airflow conditions, the average impurity rate of rice was the lowest when the airflow velocity was 9 m/s. When the flow velocity remains unchanged and the airflow inclined angle was set at 10°, the average impurity rate decreased, while the entrainment loss rate increased. The airflow velocity was negatively correlated with the impurity rate and positively correlated with the entrainment loss rate, while the airflow inclined angle was negatively correlated with the impurity rate and positively correlated with the entrainment loss rate. By designing and setting up an experimental device, an experiment was carried out with airflow velocity and airflow inclined angle as the factors, and the experimental results were consistent with the simulation results, indicating that it was reliable to study the physical behavior of rice-straw separation in the airflow field by using the DEM-CFD coupling method. Keywords: DEM-CFD, rice cleaning, airflow velocity, airflow inclined angle, experiment DOI: 10.25165/j.ijabe.20201305.5225 Citation: Ma X D, Zhao L, Guo B J, Dang H. Simulation and experiment of rice cleaning in air-separation device based on DEM-CFD coupling method. Int J Agric & Biol Eng, 2020; 13(5): 226–233.